Female Athletes and the Athletic System - Roberts-Wilbur, Janice R.; Wilbur, Michael; Morris, Joseph R. (My University, 1989)
This article is a literature review that discussed the difficulty that many female athletes have in making the athletic transition from high school to college athletics. Specific factors that affect the degree of difficulty that female athletes experience as they make the athletic transition, along with information about the rules and expectations of the athletic system and common mistakes that female athletes make, are presented to provide readers with information that may facilitate their ability to identify and understand female athletes who are particularly ineffective in negotiating the athletic transition.
Keywords: sex/gender; transitions